PENGARUH PENGOLAHAN DAN PENAMBAHAN Na2EDTA PADA TERIGU FORTIFIKASI TERHADAP KETERSEDIAAN BIOLOGIS SENG - Estu Nugroho; Ikeu Tanziha; Leily Amalia (Jurnal Gizi dan Pangan, 2013)
The objective of this research was to analyze changes in bioavailability of zinc (Zn) caused by addition of Na2EDTA and processing of fortified wheat flour. Bioavailability of zinc was tested by in vitro method as a simulation of human digestive track. The result showed that there was no significant difference in the bioavailability of zinc on wheat flour which is processed by frying (donuts), steaming (steamed bun), and baking (bread) (p>0.05). However, there was a tendency to increase the bioavailability of wheat flour processed by frying (donuts) and baking (bread) when compared to the raw dough. Raw dough had bioavailability of zinc 13.29%, after frying (donut) increase to 14.72%, and after baking (bread) increase to 17.06%. The addition of Na2EDTA also did not increase bioavailability of zinc significantly for the three types of processing (p>0.05), despite increased bioavailability of zinc on the donuts by 4.67%.